NUTRACEUTICAL EFFECT OF GINGEROL ON HAEMATOBIOCHEMICAL, LIVER ANTIOXIDANT STATUS AND PATHOLOGICAL CHANGES AGAINST PENICILLIC ACID MYCOTOXICOSIS IN BROILER CHICKENS: Pharmaceutical-Pathology - N. PAZHANIVEL; C. BALACHANDRAN (International Journal of Life Science and Pharma Research, 2014)
To find out the alleviative effect of gingerol on haematobiochemical, organ weight, hepatic lipid peroxidation, antioxidant status and pathological changes against penicillic acid mycotoxicosis in broiler chickens. Out of 80 day-old broiler chicks obtained, 72 were randomly allotted to six groups of 12 chicks each. The birds were fed with diets [(T1-control, T2- Gingerol (0.1%), T3- Gingerol (0.2%), T4- Penicillic acid (15 ppm), T5- Penicillic acid (15 ppm) + gingerol (0.1%), T6- Penicillic acid (15ppm) + gingerol (0.2%)] from 0 to 28 days of age. Remaining eight chicks were used as no toxin, no gingerol and no vaccine group (T7). On the 28th day of trial, remaining birds were sacrificed. The clinical sign observed in the penicillic acid toxin treated birds was depression. The PCV values of T2 and T3 groups decreased significantly (P<0.05) when compared to the T5 and T6 groups. The Hb values of T1, T2 and T6 were highly significantly (P<0.01) lower than that of T5 group. The nutraceutical effect of gingerol (0.1 and 0.2%) studied against PA toxicity (15 ppm) showed partial alleviation at 0.2 per cent level. Gingerol alone could induce hyperamylaesaemia (gingerol 0.1%), hypercholesterolaemia, hypertriglyceridaemia, increased BUN, creatinine, LDL, VLDL and HDL (gingerol 0.2%). Further gingerol alone induced toxic changes in the liver, kidney, crop, proventriculus. There were mild to moderate improvements in the serum biochemical parameters as well as histological lesions, gingerol at 0.1 per cent could not completely alleviate the toxic effects of penicillic acid (15 ppm). The above results indicated that incorporation of gingerol at 0.2 per cent level could reverse most of the toxic effects of penicillic acid (15 ppm).